2018
DOI: 10.1002/sscp.201700027
|View full text |Cite
|
Sign up to set email alerts
|

Volatile metabolites or pollen characteristics as regional markers of monofloral thyme honey?

Abstract: Thirty‐one monofloral thyme honeys were collected from professional beekeepers from four different regions in Greece during harvesting year 2012–2013. Aqueous solutions of honeys were subjected to headspace solid‐phase microextraction coupled to gas chromatography with mass spectrometry to record complete volatile pattern, whereas pollen screening was accomplished using the melissopalynological analysis. The primary objective was to investigate the volatile pattern and whether specific volatile metabolites or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…An optimization procedure was followed, in a preliminary experiment, in order to determine the most appropriate parameters for the extraction of volatile compounds from the headspace of prickly pear juice. These included: sample volume (5 and 10 mL), equilibrium time (10, 20, 25, and 30 min), sampling time (10 and 20 min), sample volume, extraction temperature (40, 42, and 45 °C), and salt (0, 20, and 30% w / v ) addition [18,19]. Based on (i) the number of volatiles determined, (ii) the MS qualification results, (iii) the limited furan derivatives identified, and (iv) the spectra intensity along with the agreement in volatiles identified during the analysis of replicates, the optimum analysis conditions were found to be: 25 min equilibration time, 20 min sampling time, 5 mL sample volume, addition of salt (30% w / v ), and 42 °C water bath temperature (Supplementary Table S8 and typical chromatograms (Figures S1–S8)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An optimization procedure was followed, in a preliminary experiment, in order to determine the most appropriate parameters for the extraction of volatile compounds from the headspace of prickly pear juice. These included: sample volume (5 and 10 mL), equilibrium time (10, 20, 25, and 30 min), sampling time (10 and 20 min), sample volume, extraction temperature (40, 42, and 45 °C), and salt (0, 20, and 30% w / v ) addition [18,19]. Based on (i) the number of volatiles determined, (ii) the MS qualification results, (iii) the limited furan derivatives identified, and (iv) the spectra intensity along with the agreement in volatiles identified during the analysis of replicates, the optimum analysis conditions were found to be: 25 min equilibration time, 20 min sampling time, 5 mL sample volume, addition of salt (30% w / v ), and 42 °C water bath temperature (Supplementary Table S8 and typical chromatograms (Figures S1–S8)).…”
Section: Methodsmentioning
confidence: 99%
“…The vials were maintained at 42 °C in a water bath under continuous stirring at 800 rpm during the headspace extraction. The stirring procedure usually improves the extraction efficiency [19]. For this purpose, a magnetic stirrer (cross shaped and coated with PTFE) with a diameter of 10 mm (Semadeni, Ostermundigen–Bern, Switzerland) was placed inside the vials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in Section 2.1, the percentage of pollen grains needed to classify a honey as monofloral is variable, ranging from 8% to 20% of Arbutus pollen for strawberry tree honey, >45% of Erica pollen for heather honey and >86% of Castanea pollen for chestnut honey [44]. Given the new challenges in the international market or domestic regulations, which may demand a higher percentage of dominant pollen grains for the characterization of particular monofloral honey types, volatile compound analysis may provide a faster and more accurate tool for botanical and geographical origin identification, by identifying the specific volatile metabolites [67].…”
Section: Main Volatile Compounds In Monofloral Honeys From Different mentioning
confidence: 99%
“…In a later study, Karabagias et al, [27] reported 2-phenylacetaldehyde, ethyl nonanoate, benzaldehyde, and 2-phenylethan-1-ol as dominant volatile compounds in 42 monofloral thyme honey samples from Greece. Four years later Karabagias et al, [28] reported 2-phenylacetaldehyde, 2-phenylacetonitrile, benzaldehyde, and 2-furancarboxaldehyde as characteristic volatile compounds in 31 thyme honey samples.…”
Section: Isolation Of Volatile Compoundsmentioning
confidence: 99%